Sample this [videorecording (DVD)] : the birth of hip hop - Forrer, Dan; Simmons, Gene, 1949-; Botkin, Perry, 1933-2021-
Recounts how, on the streets of the Bronx in the summer of 1973, DJ Herc took the percussion breaks from an obscure album by the Incredible Bongo Band and extended them by playing them back to back.